Circles of Meaning: Reading/Writing a Mother's Life - Neale, Lesley (Curtin University, 2015)
The thesis Circles of Meaning consists of two components: a creative work Kate Annie (biography & fiction) and an exegesis: Reading/Writing a Mother’s Life. The exegesis examines the work of three contemporary women writers and discusses ethical issues in women’s life writing. Both parts of the thesis respond to the research question: How can archival evidence, narrative strategies and memory be used to narrate little known family history from an invested position?